ANALISIS PERBANDINGAN DAYA DUKUNG PONDASI TIANG PANCANG BERDASAR HASIL UJI SPT DAN PENGUJIAN DINAMIS - Santoso, Hinawan Teguh; Hartono, Juandra (Jurnal Riset Rekayasa Sipil, 2020)
The foundation work is one of the main works in bridge construction. Failure of the foundation will be fatal for the entire bridge construction. Therefore, it is necessary to test the bearing capacity of the pile to determine the installed foundation capacity. The most accurate and most expensive method for determining the bearing capacity of a pile is a static load test, which is a full-scale trial method of giving a load 2 or 3 times greater than the designed load. Another method that is more economical and entirely accurate is using the High Strain Dynamics Pile Test (HSDPT) or often called the Pile Driving Analyzer (PDA) Test. This PDA test took a sample of 18 points of 600 mm diameter pre-stressed concrete piles on the Kaligawe Bridge located on Jalan Kaligawe KM 2+350, Semarang, Central Java. Based on the core drilling results, the soil layer was dominated by clay with an N-SPT value < 30 to a depth of 45 meters. The average bearing capacity of PDA test results is 432.4 tons or 0.4% greater when compared to the empirical approach based on N-SPT value (430.7 tons). The bearing capacity of the CAPWAP analysis is 401.0 tons or 7.3% less when compared to the PDA test, because the PDA test results are further processed using Signal Matching Analysis (SMA). CAPWAP analysis shows that the bearing capacity of piles is dominated by friction resistance by 71.7% and end resistance by 28.3% or by 4.4% difference when compared to the empirical approach, where the friction resistance value is 67.3% and end resistance is 32.7%. In general, it can be said that the PDA test is reliable enough to confirm the bearing capacity of the pile foundation that has been installed in the field.